2020
DOI: 10.3390/vaccines8030380
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B Cells and Their Cytokine Profile in HCV-Related Hepatocellular Carcinoma: Association with Regulatory T Cells and Disease Progression

Abstract: Although regulatory B cells (Bregs) have been proven to play a suppressive role in autoimmune diseases, infections and different tumors, little is known regarding hepatocellular carcinoma (HCC), especially in hepatitis C-related settings. Herein, we analyzed the frequency of circulating Bregs, serum levels of IL-10, IL-35 and B-cell activating factor (BAFF) and investigated their association with regulatory T cells (Tregs) and disease progression in HCV-related HCC. For comparative purposes, four groups were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…The SOX process is an orthodox technique that is extensively helpful in removing oil from the matrix, which is utilized when the compound of interest has restricted solubility in a solvent while the impurities are insoluble in the solvent [22]. Bajer et al [29] extracted capsaicinoids from several chili samples via the SOX procedure, with methanol as the solvent and an extraction time of 2 h. The same SOX procedure was utilized in a study by Liu et al [30], in which the extraction of 1.0 g of a C. annuum sample was achieved with 50 mL of methanol for 2 h.…”
Section: Soxhlet (Sox) Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOX process is an orthodox technique that is extensively helpful in removing oil from the matrix, which is utilized when the compound of interest has restricted solubility in a solvent while the impurities are insoluble in the solvent [22]. Bajer et al [29] extracted capsaicinoids from several chili samples via the SOX procedure, with methanol as the solvent and an extraction time of 2 h. The same SOX procedure was utilized in a study by Liu et al [30], in which the extraction of 1.0 g of a C. annuum sample was achieved with 50 mL of methanol for 2 h.…”
Section: Soxhlet (Sox) Extractionmentioning
confidence: 99%
“…The process of PLE is regularly performed at a raised temperature and pressure, allowing the high solubility of the compound in the solvent whilst maintaining the solvent beneath its boiling point, and thus leading to a high permeation of the solvent into the sample matrix [24,36]. Many scientists have espoused the PLE technique [29,30,37]. Barbero et al [37] improved a PLE protocol with the extraction solvent of water, methanol, and ethanol with a temperature of 200 • C and pressure of 100 atm.…”
Section: Ple (Pressurized Liquids Extraction)mentioning
confidence: 99%
“… 21 B regs play an immunomodulatory and suppressive role against auto-inflammation and auto-reactivation, as was noticed in other diseases, via IL-10 dependent and independent mechanisms, through maintaining T regulatory cells and negatively regulating T cell differentiation. 17 , 18 , 27 Thus, the observed drop in B regs numbers may be accounting for the increased risk of acquiring BD. An inverse relationship between the total number of B cells and the disease activity scores was present in the current study which was also reported by van der Houwen et al who observed shifting of B cells from the blood to the sites of inflammation, and normalization of the numbers following anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages and neutrophils eliminate the pathogen and infected cells through phagocytosis. Even though all these mechanisms are important for viral elimination, an over-reactive immune response may contribute to disease pathogenesis [ 59 , 60 , 61 ].…”
Section: Innate Immunity During Covid-19mentioning
confidence: 99%